2022
DOI: 10.3390/cells11213468
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin Modifies Gut Microbiota and Attenuates Inflammation in Parkinson’s Disease: Preclinical and Clinical Studies

Abstract: Patients with Parkinson’s disease (PD) exhibit distinct gut microbiota, which may promote gut-derived inflammation. Rifaximin is a nonabsorbable antibiotic that can modify gut microbiota. The present study investigated the effect of rifaximin on gut microbiota and inflammation status in PD. The study examined the effect of long-term rifaximin treatment on in vivo transgenic PD mice (MitoPark) and short-term rifaximin treatment on patients with PD. Rifaximin treatment caused a significant change in gut microbio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 67 publications
0
32
0
Order By: Relevance
“…By taking rifaximin, a non-absorbable antibiotic, the gut microbiota can be modified. Patients with PD and higher baseline inflammation levels may have experienced benefits from taking rifaximin [252]. The negative association between ibuprofen and PD risks implies that ibuprofen has the potential to act as a neuroprotective agent against PD (see Table 2) [248].…”
Section: Discussionmentioning
confidence: 99%
“…By taking rifaximin, a non-absorbable antibiotic, the gut microbiota can be modified. Patients with PD and higher baseline inflammation levels may have experienced benefits from taking rifaximin [252]. The negative association between ibuprofen and PD risks implies that ibuprofen has the potential to act as a neuroprotective agent against PD (see Table 2) [248].…”
Section: Discussionmentioning
confidence: 99%
“…Association with Non-motor Symptoms: Non-motor symptoms, including depression and anxiety, significantly detract from the quality of life for individuals with PD and often manifest prior to the disease's motor symptoms. This timing suggests a potential connection to early pathological changes within PD (13,18,20,21,24,26,28,31,33,34,36,39,42,43,45,47,50,51,53,55,58,59,61). The gut-brain axis mediates the gut microbiota's effect on mood and behavior, with specific bacterial strains producing neurotransmitters like serotonin and dopamine, crucial for mood regulation (9,13,16,18,20,22,25,27,30,32,35,37,43,45,50,52,56,58).…”
Section: Behavioral and Cognitive Effects Of Gut Microbiota In Pdmentioning
confidence: 96%
“…Dysbiosis-induced inflammation could intensify neurodegeneration, hastening cognitive deterioration (5,6,10,13,21,25,32,36,40,56,59). Additionally, neurotoxic metabolites produced by specific pathogenic bacteria might directly affect brain function, implicating gut microbiota in PD's cognitive deficits (2, 54).…”
Section: Behavioral and Cognitive Effects Of Gut Microbiota In Pdmentioning
confidence: 99%
“…Antibiotics have also been found to significantly improve motor dysfunction and alleviate neuroinflammation by increasing the relative abundance of Akkermansia and Lachnospiraceae and SCFA levels in the faeces of MPTP-induced and transgenic PD mouse models [ 172 174 ]. A 12-month study found that creatine and minocycline can delay the disease progression in PD patients [ 175 ].…”
Section: Potential Clinical Approaches Targeting the Microbiome In Ndsmentioning
confidence: 99%